Self-organization of human dorsal-ventral forebrain structures by light induced SHH - Riccardo De Santis (Nature Portfolio, 2021)
Organizing centers act to pattern surrounding tissues during embryogenesis through the secretion of morphogens. Here the authors model human organizers using light stimulus to geometrically confine SHH expression in differentiating hESCs, generating spatially resolved proximal distal patterns.